Efficient Neutral Nitrate-to-Ammonia Electrosynthesis Using Synergistic Ru-Based Nanoalloys on Nitrogen-Doped Carbon - Huang, Lisi; Zhang, Pingzhi; Ge, Xin; Wang, Bingyu; Yuan, Jili; Li, Wei; Wang, Liang (Shanghai Jiao Tong Univ Press, 2025)
Electrocatalytic nitrate reduction reaction (NO3RR) represents a sustainable and environmentally benign route for ammonia (NH3) synthesis. However, NO3RR is still limited by the competition from hydrogen evolution reaction (HER) and the high energy barrier in the hydrogenation step of nitrogen-containing intermediates. Here, we report a selective etching strategy to construct RuM nanoalloys (M = Fe, Co, Ni, Cu) uniformly dispersed on porous nitrogen-doped carbon substrates for efficient neutral NH3 electrosynthesis. Density functional theory calculations confirm that the synergic effect between Ru and transition metal M modulates the electronic structure of the alloy, significantly lowering the energy barrier for the conversion of *NO2 to *HNO2. Experimentally, the optimized RuFe-NC catalyst achieves 100% Faraday efficiency with a high yield rate of 0.83 mg h(-1) mg(cat)(-1) at a low potential of - 0.1 V vs. RHE, outperforming most reported catalysts. In situ spectroscopic analyses further demonstrate that the RuM-NC effectively promotes the hydrogenation of nitrogen intermediates while inhibiting the formation of hydrogen radicals, thereby reducing HER competition. The RuFe-NC assembled Zn-NO3- battery achieved a high open-circuit voltage and an outstanding power density and capacity, which drive selective NO3- conversion to NH3. This work provides a powerful synergistic design strategy for efficient NH3 electrosynthesis and a general framework for the development of advanced multi-component catalysts for sustainable nitrogen conversion.
Keywords: Synergic effect; Selective etching; Nanoalloys; Porous nitrogen-doped carbon; Neutral NH3 electrosynthesis